Herbal Medicine Containing Licorice May Be Contraindicated for a Patient with an HSD11B2 Mutation. (20th February 2011) - Harahap, Indra Sari Kusuma; Sasaki, Naoko; Gunadi,; Yusoff, Surini; Lee, Myeong Jin; Morikawa, Satoru; Nishimura, Noriyuki; Sasaki, Tomohiro; Usuki, Seiichiro; Hirai, Midori; Ohta, Mika; Takaoka, Yutaka; et al.
Abstract : Licorice ingestion, as well as mutations in the HSD11B2 gene, inhibits 11 β -hydroxysteroid dehydrogenase type 2 (11 β HSD2) enzyme activity, causing the syndrome of apparent mineral corticoid excess (AME). However, the combined effect of licorice ingestion and an HSD11B2 mutation has never been reported, until now. In this study, we demonstrated that licorice ingestion can produce overt hypertension in an individual without medical history of hypertension who is heterozygous for wild-type and mutant HSD11B2 genes. Our patient was a 51-year-old female with serious hypertension who had been taking herbal medicine containing licorice for more than one year. She was clinically diagnosed as having licorice intoxication, because she did not present with hypertension after ceasing the herbal medicine . Molecular analysis showed that she carried a missense mutation, c.40C>T, in HSD11B2 . In conclusion, licorice ingestion is an environmental risk factor for hypertension or AME state in patients with a mutation in HSD11B2. Carrying a mutation in HSD11B2 is, conversely, a genetic risk factor for licorice-induced hypertension or AME state. Herbal medicine containing licorice may, therefore, be contraindicated in patients with an HSD11B2 mutation.